Respuesta :
x^2 + 4x - 4 = 0
(x + 2)^2 - 4 - 4 = 0
(x + 2)^2 = 8
x + 2 = +/- √8
x = -2 + √8 , - 2 - √8
x = -2 + 2√2 , -2 - 2√2 (answer)
we can't factor so use quadratic formula
for [tex]ax^2+bx+c=0[/tex] [tex]x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}[/tex]
we have [tex]x^2+4x-4=0[/tex]
a=1, b=4, c=-4
[tex]x=\frac{-4 \pm \sqrt{4^2-4(1)(-4)}}{2(1)}[/tex]
[tex]x=\frac{-4 \pm \sqrt{16+16}}{2}[/tex]
[tex]x=\frac{-4 \pm \sqrt{32}}{2}[/tex]
[tex]x=\frac{-4 \pm 4\sqrt{2}}{2}[/tex]
[tex]x=-2 \pm 2\sqrt{2}[/tex]
x=-2+2√2 and x=-2-2√2 are the values of x that satisfy the equation